2018
DOI: 10.1007/s11934-018-0751-x
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the Envelope: Laparoscopic Nephrectomy as Outpatient Surgery

Abstract: Laparoscopic nephrectomy for patients who have kidney cancer can be performed as an outpatient surgery in well-selected, well-educated, and well-informed patients in a well-prepared hospital culture. Patient confidence, pain, and hospital culture are the most important limiting factors to the performance of laparoscopic nephrectomy as an outpatient procedure. Controlling these factors leads to a high success rate for the outpatient procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…Moreover, one can argue that postoperative hospital stay is not only depending on the surgical technique, and it can be influenced by factors other than preoperative parameters. In this regard, it has been shown that outpatient transperitoneal laparoscopic nephrectomy can be safely implemented in well informed and selected patient, given appropriate hospital setup 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, one can argue that postoperative hospital stay is not only depending on the surgical technique, and it can be influenced by factors other than preoperative parameters. In this regard, it has been shown that outpatient transperitoneal laparoscopic nephrectomy can be safely implemented in well informed and selected patient, given appropriate hospital setup 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Eight reviews (Azawi et al, 2018; Bourke et al, 2015; Di Rollo et al, 2015; Faris et al, 2019; Hage & Lorensen, 2005; Kruzik, 2009; Parahoo et al, 2015; Simpson, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In men, the incidence of urological cancers appears to increase starting at middle age, peaking toward the end of life, whereas in women, this trend is less obvious (MacLennan et al, 2017). Consequently, urological procedures are not uncommon (Davies et al, 2015); active treatments, such as prostatectomy, nephrectomy, or cystectomy can have potentially negative effects and often cause urinary, bowel, and sexual side effects, which might contribute to reduced health-related quality-of-life (Azawi et al, 2018; Bourke et al, 2015; Parahoo et al, 2015; Parker et al, 2009; Song et al, 2012; Weinberg et al, 2012; Wootten et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent articles have reported outpatient procedures in laparoscopic nephrectomy [27], colectomy [28], total hip and knee arthroplasty [29], and laparoscopic Heller myotomy [30]. Although outpatient procedures are theoretically the natural end consequence of a fully developed ERAS program, it should be emphasized that the concept is based on ‘first better - then faster’, and that safety, especially in high-risk patients, must be prioritized before focusing on length of stay [31 ▪ ].…”
Section: Improvements In Perioperative Carementioning
confidence: 99%